2019
DOI: 10.1002/mrd.23257
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous pluripotent factor expression after reprogramming cat fetal fibroblasts using inducible transcription factors

Abstract: Incomplete transgene‐silencing remains a challenge in the generation of induced pluripotent stem cells (iPSC) in felids—a critical family in biomedical and biodiversity conservation science. In this study doxycycline‐inducible transgenes (NANOG, POU5F1, SOX2, KLF4, and cMYC) were used to reprogram cat fetal fibroblasts with the objective of obtaining iPSC with fully silenced transgenes. Colony formation was slower (14 vs. 8 days) and at lower efficiency than mouse embryonic fibroblasts (0.002% vs. 0.02% of see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…In cats, Gata6 is assumed to be involved in differentiation similar to humans, but that has yet to be examined. Studies have described the presence of Gata6 in feline induced pluripotent stem cells [41] and in cat embryos [36], but ours is the first study to report the presence of Gata6 in feline adipose MSCs. SOX17, identified in human adipose derived MSCs [43], is involved in the capacity of the cells to differentiate into endoderm and eventually to hepatocytes [44] or pancreatic tissue [33].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In cats, Gata6 is assumed to be involved in differentiation similar to humans, but that has yet to be examined. Studies have described the presence of Gata6 in feline induced pluripotent stem cells [41] and in cat embryos [36], but ours is the first study to report the presence of Gata6 in feline adipose MSCs. SOX17, identified in human adipose derived MSCs [43], is involved in the capacity of the cells to differentiate into endoderm and eventually to hepatocytes [44] or pancreatic tissue [33].…”
Section: Discussionmentioning
confidence: 67%
“…In comparison with canine cells, feline amniotic MSCs showed a much lower expression of Sox2 and less immunostaining of the protein compared to canine amniotic stem cells [39]. In addition, a number of labs have shown that induced pluripotent stem cells derived from feline fibroblasts express Sox2 [40,41]. However, the presence of Sox2 in feline adipose-derived MSCs is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iPSCs have been developed from porcine [16], equine [17], canine [18], bovine [19], galline [20], caprine [21], ovine [22], and feline [23] tissue. Successful iPSC production from domestic species was first reported in 2009 by Wu and colleagues in porcine, and the field has since expanded to other species (Fig.…”
Section: Ipsc Production and Characterizationmentioning
confidence: 99%
“…1). iPSC derivation protocols have been developed in species including porcine [16], equine [17], canine [18], bovine [19], galline [20], caprine [21], ovine [22], and feline [23]. Aside from their importance in treating veterinary pathologies, porcine, canine, and equine models have been shown to be valuable for the study and treatment of human disease [24][25][26].…”
Section: Introductionmentioning
confidence: 99%